Web advertising : the effectiveness of banner ad - Shamsuddin, Ahmad Sharifuddin (1999)
It has been suggested that the Internet represents the most significant development in communication technology since the advent of Television. With growing numbers of users at staggering rate worldwide, the implications of such medium are becoming increasingly significant for the marketing discipline. Even though the IT industry in Malaysia is still in its infancy, the speed of growth has been accelerated by the development of the Multimedia Super Corridor. In accordance with the rapid growth if the IT industry in Malaysia, this paper attempt to study the power of web as a marketing tool particularly in the field of advertising. So this paper is important because it tries to explain the characteristics of effective web advertising, the banner ad in particular. To carry out this research, samples from the student of Universiti Teknologi Malaysia were selected. This group of people were generally perceived as heavy users of the Internet. The findings of this research indicated that there are three main areas that need to be focus on whenever designing a web ad. Those are graphics of the ad, the positioning of the ad and the correct size of the ad. Also highlighted are the differences between the web and traditional media. Finally, while realising that there are no golden rules to be followed, web advertisers should not fail to put on more effort to study the web ad more thoroughly and perfecting the are of web advertisement.